Fabrication of Phloridzin Loaded Poly(ε-caprolactone) Nanoparticles as a Wound Dressing Material Candidate for Diabetic Foot Infections - Budama-Kilinc, Yasemin (AMER SCIENTIFIC PUBLISHERS, 2019)
Phloridzin is found in the shell and bodies of the apple trees. It has a strong antioxidant property, and its pharmacological features also allow the compound to be used for medical purposes. The compound is a potential active substance, especially for the treatment of type diabetes. In this study, phloridzin-loaded poly(epsilon-caprolactone) nanoparticles were prepared and characterized in terms of particle size (zeta sizer), binding (ultraviolet-visible spectroscopy), molecular (Fourier transform infrared spectroscopy), thermal (thermogravimetry), and microstructural (transmission electron microscopy) properties. The loading and encapsulation efficiency of phloridzin-loaded poly(epsilon-caprolactone) nanoparticles were also determined, and their controlled release profile was revealed. Moreover, their concentration-dependent DPPH radical scavenging assay, and their interaction with DNA was investigated. The DNA binding (with calf thymus) and cleavage (pBR322 plasmid DNA properties) activities of the phloridzin-loaded poly(epsilon-caprolactone) nanoparticles were analyzed. Besides, their antibacterial activities of phloridzin-loaded poly(epsilon-caprolactone) nanoparticles were investigated to test if they can be utilized as a wound dressing material for diabetic foot infections.
Keywords: Phloridzin; Poly(epsilon-caprolactone); Diabetic Foot Infection; Wound Dressing; Nanoparticle; Antioxidant; Antibacterial; ANTIMICROBIAL ACTIVITY; ANTIOXIDANT ACTIVITY; ESSENTIAL OIL; DNA-BINDING; GLUCOSE; POLYETHYLENE; PHLORETIN; COMPLEX; DRUG; Science & Technology - Other Topics; Materials Science; Physics